2022
DOI: 10.3390/su14148387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity and Temperature on the Seed Germination and Seedling Growth of Desert Forage Grass Lasiurus scindicus Henr.

Abstract: Lasiurus scindicus Henr. is one of the most important forage grass species of the Arabian deserts. Temperature and soil salinity are well known to influence the germination and seedling development of various forage species. Therefore, in the current study, the effect of temperature and salinity and their interaction on the germination parameters, seedling growth, and physiological parameters of L. scindicus were evaluated. For this reason, L. scindicus seeds were treated with five salinity concentrations (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
(115 reference statements)
2
4
0
Order By: Relevance
“…The statistical analysis in Table 3 showed that plant species, seasons, and their interactions with the amounts of all photosynthetic pigments in the three plant species had highly significant effects (P < 0.01). Our findings were consistent with those of El-Absy [6], Uvalle Sauceda et al [66], Devi et al [67], Khater et al [68], Malik et al [69], Neamah and Jdayea [70], in which the findings likewise revealed seasonal variations had significant effects on all photosynthetic pigments in different plant species. The contents of chlorophyll a (Chl.a), chlorophyll b (Chl.b) and Chl.a+b showed a significant increase in H. muticus type, followed by T. polium and A. setifera species.…”
Section: Plant Analysissupporting
confidence: 92%
“…The statistical analysis in Table 3 showed that plant species, seasons, and their interactions with the amounts of all photosynthetic pigments in the three plant species had highly significant effects (P < 0.01). Our findings were consistent with those of El-Absy [6], Uvalle Sauceda et al [66], Devi et al [67], Khater et al [68], Malik et al [69], Neamah and Jdayea [70], in which the findings likewise revealed seasonal variations had significant effects on all photosynthetic pigments in different plant species. The contents of chlorophyll a (Chl.a), chlorophyll b (Chl.b) and Chl.a+b showed a significant increase in H. muticus type, followed by T. polium and A. setifera species.…”
Section: Plant Analysissupporting
confidence: 92%
“…The seeds were incubated in the dark for 7 days at 20° C. Every day the number of germinating seeds was counted. Germination percentage (GP) was calculated using the following equation [ 34 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Every day the number of germinating seeds was counted. Germination percentage (GP) was calculated using the following equation [34]:…”
Section: The Effect Of Sam On Seeds Germinationmentioning
confidence: 99%